Assessment of the quality of life in patients with chronic obstructive pulmonary disease according to concomitant disorders of psycho-emotional sphere - Dovgan, Alina; Konstantynovych, Tetyana (ScienceRise: Medical Science, 2017)
Aim – to study quality of life (QOL) indicators in patients with chronic obstructive pulmonary disease (COPD) at different types and expressiveness of concomitant psycho-emotional disorders. Materials and methods. There were examined 206 patients with COPD (158 (76,7 %) men and 48 (23,3 %) women, whose mean age was 64,4±0,8 years, mean disease duration – 8,8±0,4 years) using clinical-functional and questionnaire methods of research. The psychic status of respondents was determined using the complex of standardized questionnaire methods. QOL was assessed using the Ukrainian version of the international questionnaire on QOL MOS SF-36. The statistical processing of data was realized using the package of statistical programs SPSS 20.0 for Windows by parametric and non-parametric methods according to the type of variables distribution. Results. It was established, that patients with COPD had statistically reliably higher mean values than practically healthy persons by scales of neurotization ((44,97±1,27) %, р=0,005), state anxiety ((42,82±0,64) points, р<0,001), trait anxiety ((44,95±0,63) points, р <0,001) and depressive states ((41,00±0,65) points, р<0,001). There were established the prevalence of psycho-emotional disorders in patients with COPD: neurotization (26,2 %), state anxiety (37,9 %), traitanxiety (49,5 %), depressive states (16,5 %). It was revealed that patients with COPD have reliably lower mean values than practically healthy persons by all indicators of physical, psychic and general statuses of QOL and change health comparing with the previous year. It was established, that each separate psycho-emotional disorder essentially influences QOL indicators of patients with COPD that is manifested in the reliable decrease of mean values by all scales of MOS SF-36 form. Conclusions. In the result of the study there were assessed QOL indicators of patients with COPD and also established their dependence on the type and expressiveness of concomitant psycho-emotional disorders